Pengaruh Anggaran Terhadap Kinerja Manajerial pada PT. Duta Marga Lestarindo - Lukman Nasution; Reza Nurul Ichsan (Mahesa Research Center, 2022)
This study aims to determine and analyze the influence of budget on managerial performance at PT. Ambassador Marga Lestarindo Medan. So the formulation of the problem is